Autonomous Directional Motion of Actin‐Containing Cell‐Sized Droplets. (16th November 2020) - Haller, Barbara; Jahnke, Kevin; Weiss, Marian; Göpfrich, Kerstin; Platzman, Ilia; Spatz, Joachim Pius
Abstract : Cell motility is potentially the most apparent distinction of living matter, serving an essential purpose in single cells and multicellular organisms alike. Thus, the bottom‐up reconstitution of autonomous motion of cell‐sized compartments remains an exciting but challenging goal. Herein, actin‐driven Marangoni flows are engineered to generate rotational and translational motility of surfactant‐stabilized emulsion droplets. The interaction between actin filaments and the negatively charged block‐copolymer Krytox is identified as the driving force for Marangoni flows at the droplet interface. Tuning the actin–Krytox interplay, sustained autonomous unidirectional droplet rotation with 1.7 rot h −1 is achieved. Ultimately, this rotational motion is transformed into a translational rolling motion by introducing interactions between the droplets and the surface of the observation chamber. Accordingly, translational motility of actin‐containing droplets at velocities of 0.061 ± 0.014 μm s − 1 is reported herein and an overall displacement of several hundreds of micrometers within 30 min is observed. These self‐propelled systems with biologically active molecules demonstrate how motility could be implemented for synthetic cells. Abstract : Herein, actin‐driven Marangoni flows are engineered to generate rotational and translational motility of surfactant‐stabilized water‐in‐oil droplets. Based on the interaction of actin filaments and the negatively charged block‐copolymer surfactants, sustained autonomous unidirectional droplet rotation is achieved. Ultimately, this rotational motion is transformed into a translational rolling motion with an overall displacement of several hundreds of micrometers.